1978
DOI: 10.1111/j.1365-2125.1978.tb01616.x
|View full text |Cite
|
Sign up to set email alerts
|

Amitriptyline‐ and mianserin‐induced changes in acquisition of paired‐ association learning‐task.

Abstract: I The double-blind study on twenty healthy students was an attempt at assessing the effects of 2-week's treatment with amitriptyline (25 mg three times a day) and mianserin (10 mg three times a day), each alone or separatively inbibed with alcohol (0.5 g/kg) on the immediate memory and on the acquisition of a paired-association learning-task. 2 Amitriptyline impaired both the short-term memory-span and acquisition, and alcohol potentiated these effects. The action of mianserin did not deviate significantly fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1980
1980
1996
1996

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Again Hindmarch et al [69] agree on this point. The findings obtained by Seppala [27] , Liljequist et al [71] and Seppala and Visakorpi [72] can also be referred to in this context, as these authors could demonstrate that the anticholinergic properties are related to memory functions, not however, to psychomo tor performance.…”
Section: Discussionmentioning
confidence: 82%
“…Again Hindmarch et al [69] agree on this point. The findings obtained by Seppala [27] , Liljequist et al [71] and Seppala and Visakorpi [72] can also be referred to in this context, as these authors could demonstrate that the anticholinergic properties are related to memory functions, not however, to psychomo tor performance.…”
Section: Discussionmentioning
confidence: 82%
“…Of the remaining two, one reports that 30 mg daily for 2 weeks to healthy volunteers had no effect on memory while detrimental effects were noted on other measures (Liljequist et al, 1978). Curran et al (1986), however, did note adverse effects of the drug when given to healthy volunteers.…”
Section: Mianserinmentioning
confidence: 96%
“…Seven reported some detrimental effects (Liljequist et al, 1978;Peck el al., 1979;Branconnier et al, 1982;Linnoila et al, 1983;Warrington et al, 1984;Curran et al, 1988;Moskowitz and Burns, 1988). The other two found no influence on test scores, although in both assessment was confined to a single measure of short-term memory (Bye et al, 1978;Patat et al, 1988).…”
Section: Amitriptylinementioning
confidence: 98%
“…A concept identification task has been used in several studies (Hindmarch & Parrott, 1978;1980a;1980b) but performance ratings were found to be too dependant upon the experience of the test administrator to warrant the more general usage of such a measure. Symbol arrangement (Liljequist, Seppala & Mattila, 1978) has proved to be a less sensitive test than either the DSST or symbol cancelling tasks described earlier.…”
Section: Central Processingmentioning
confidence: 87%
“…Using verbal conditioning procedures, Gupta (1973) has separated the facilitatory effect of dexedrine from the inhibitory activity of chlorpromazine and phenobarbitone. Using both digit span and paired-associate learning techniques Liljequist et al (1978) have shown that amitriptyline 25 mg, but not mianserin 10 mg or placebo impaired performance.…”
Section: Memory and Learningmentioning
confidence: 99%